Neutron induced transmutations in tungsten for fusion energy applications: Preliminary results - Chatzikos, Vasileios; Savva, Marilia I.; Vasilopoulou, Theodora; Mergia, Konstantina; Stamatelatos, Ion E.; Terentyev, Dmitry; Stankovskiy, Alexey; Messoloras, Spyros (HNPS Advances in Nuclear Physics, 2020)
Scope of the work is the validation of the methodology applied for the prediction of induced activity and transmutation products in Tungsten due to neutron irradiation. Three types of tungsten products were irradiated at the BR2 material test reactor, SCK-CEN, Belgium, at doses of 0.12 and 0.18 displacements per atom (dpa) at the irradiation temperatures of 600, 800, 900 and 1200 °C. Gamma spectroscopy enabled the determination of the concentration of activities of the isotopes 185W, 181W, 188W, 188Re and 182Ta in the irradiated samples. The results were compared with FISPACT-II calculations and in the case of 185W a satisfactory agreement between the calculated and experimental data was observed.